Evaluation of the influence of supportive education on the religious beliefs and practices of cervical cancer patients in managing the disease at Tertiary Health Institutions in Ebonyi State, Nigeria - Augusta N Emeh; Ejovi Akpojaro; Christiana I. Elusoji; Ngozi R. Osunde; Eweka Abieyuwa; Roseline U.Agogo; Mary Munge; Emina Anwuli; Mary A. Iniomor; Emmanuela C. Anyanwu; Clementina N. Eze; Ohanme Eugene Ohams (International Journal of Tropical Medicines, 2025)
This study investigated how 60 cervical cancer patients in a tertiary care facility in Ebonyi State, Nigeria How to use Cervical Cancer Support Education (CCSE) to manage their care. Using a quasi-experimental design, 60 participants were divided into an intervention group from two health institutions and a control group from the National Obstetric Fistula Centre. The research used a quasi-experimental design and collected data over a 13-month period using a questionnaire developed by the researchers. climb The main focus was to assess whether CCSE could improve the self-management practices of patients in the intervention group. The results revealed significant improvements in self-care management in the intervention group compared to the control group. This improvement is due to the CCSE program, which provides students with the knowledge and skills needed to manage their symptoms. The study concluded that CCSE is effective in enhancing health care management in patients with cervical cancer. It also recommends integrating CCSE into routine oncology care to improve patient outcomes. The study also highlights the need for capacity-building initiatives aimed at physicians and nurse To ensure that CCSE is delivered effectively This will help improve long-term patient care. The study concluded that CCSE effectively enhanced healthcare management among cervical cancer patients and recommended its integration into oncology care. Additionally, building the capacity of physicians and nurses to deliver CCSE was emphasized.
Keywords: Cancer; Capacity-building; cervical cancer; oncology; self-care management